Ultraviolet Laser Diode Ablation Process for CMOS 45 nm Copper Low-K Semiconductor Wafer - Shi K.W.; Kar Y.B.; Talik N.A.; Yew L.W. (Elsevier Ltd, 2023)
Ablation; CMOS integrated circuits; Composite micromechanics; Copper; Design of experiments; Laser ablation; Laser pulses; Micromachining; Pulse repetition rate; Semiconductor diodes; Semiconductor lasers; Silicon wafers; Solid state lasers; Advanced dicing tehcnology; Laser dicing; Laser grooving; Laser micro-machining; Laser scribing; semicoonductor wafer; Ultra low-k; Ultraviolet lasers